Pengembangan Kemampuan Bahasa Ekspresif Anak Melalui Membaca Nyaring Buku Berbasis Nilai Agama dan Moral di TKIT Permata Bunda Merauke - Ajat Ajat; Ruyanah Ruyanah; Resti Widayanti; Iis Nuraeni Komara; Zulfi’a Ekaningrum (Syntax Idea)
The development of expressive language needs to be developed so that children can express their opinions and thoughts to other people. Children's expressive language development can be developed through the reading aloud method. This research aims to examine the development of children's expressive language skills through reading aloud at TKIT Permata Bunda. The research method used is descriptive qualitative. The subjects of this research were group A children aged 4-5 years and two teachers. Data collection techniques include interviews, documentation and direct observation. The results of the research show that developing children's expressive language skills can be done through the activity of reading aloud books based on religious and moral values. The implementation stage includes planning by selecting books according to the child's development level and containing religious and moral values. The next stage is implementation in the form of introducing the book, reading the story book aloud with the right intonation, holding a discussion and asking stimulating questions and motivating the child to retell the story. Next, the teacher carries out an assessment to determine the achievement of expressive language development.